Ectopic prostatic tissue involving the omentum and presenting with intussusception and small intestinal obstruction: A report of a rare case with a review of the literature - Tyler S. Yeager; Brandon C. Stroh; Raphael El Youssef; Paul J. Michaels (Elsevier, 2022)
Ectopic prostatic tissue has been uncommonly reported within the literature in the past, typically described involving areas within the lower genitourinary tract. Although patients can occasionally present with urinary symptoms related to the ectopic prostatic tissue, many of these cases are identified incidentally. Ectopic prostatic tissue, depending on the location, can represent a diagnostic dilemma for both clinicians and pathologists and generate a broad differential diagnosis that includes non-neoplastic and neoplastic proliferations, including both benign and malignant neoplasms.Here we report a case of an 85-year-old male who presented with nausea, vomiting, and abdominal pain and was found to have an omental mass causing a distal small intestinal obstruction on pre-operative radiologic imaging, confirmed on exploratory laparotomy. A metastatic carcinoma was suspected clinically, as the patient had a known cystic lesion diffusely involving the pancreas. However, gross and histological evaluation of the specimen revealed an omental mass adherent to the small intestinal serosa that showed central infarction and features diagnostic of ectopic prostatic tissue, confirmed with immunohistochemical stains.